What Chicago community organizations needed to implement COVID-19 interventions: lessons learned in 2021 - Moskowitz, David A.; Silva, Abigail; Castañeda, Yvette; Battalio, Samuel L.; Hartstein, Madison L.; Murphy, Anne Marie; Ndebele, Sithembinkosi; Switalski, Matthew; Lomahan, Sarah; Lacson, Leilani; Plum, Abigail; Canty, Emma; et al. (Frontiers in Public Health, 2023)
As the COVID-19 pandemic placed a spotlight on the health inequities in the United States, this study aimed to determine the local programmatic needs of community organizations (CO) delivering COVID-19 interventions across Chicago. Methods: In the summer of 2021, the Chicagoland CEAL Program interviewed 34 COs that were providing education, testing, and/or vaccinations in communities experiencing poor COVID-19 outcomes. The interviews were analyzed thematically and organized around logistical challenges and funding/resource needs. Results: The COs routinely offered testing (50%) or vaccinations (74%), with most (56%) employing some programmatic evaluation. Programs utilizing trusted-messenger systems were deemed most effective, but resource-intensive. CO specific needs clustered around sustaining effective outreach strategies, better CO coordination, wanting comprehensive trainings, improving program evaluation, and promoting services and programs. Conclusions: The COs reached populations with low-vaccine confidence using trusted messengers to overcome mistrust. However, replenishment of the resources needed to sustain such strategies should be prioritized. Leveraging the Chicagoland CEAL Program to help negotiate community organizations’ interorganizational coordination, create training programs, and provide evaluation expertise are deliverable supports that may bolster COVID prevention. Policy Implications: Achieving health justice requires that all institutions of power participate in meaningful community engagement, help build community capacity, and infuse health equity throughout all aspects of the research and program evaluation processes.